Origin of nucleolus-like bodies found in the nucleoplasm and cytoplasm of Vicia faba meristematic cells. - Sato, S; Willson, C; Dickinson, H (1988)
Cytohistochemical staining and RNase-gold labelling have been applied to root-tip meristematic cells of Vicia faba to study the origin and biological significance of 2 types of inclusions: one seen in the nucleoplasm and the other in the cytoplasm of early telophase cells. They have been termed "dense bodies" and "cytoplasmic nucleolus-like bodies" (NLB), respectively. Both types of inclusions respond positively to silver staining and ribonucleoprotein (RNP) staining in a similar fashion to nucleolus. Interestingly, the dense bodies label heavily with the RNase-gold complex, as does the nucleolus, while the cytoplasmic NLB have no affinity with the label. In most cases, the dense bodies label more heavily than the nucleolus. Light microscope surveys reveal that the dense bodies sometimes appear to be released from the surface of the nucleolus. On the other hand, prenucleolar material showing the same silver staining and RNP preferential staining characteristics as the dense bodies begin to accumulate on the surface of chromosomes in mid-anaphase. This material does not label with RNase-gold. These data are discussed in terms of the hypothesis that the dense bodies are derived from the nucleolus by direct budding or fragmentation, and the cytoplasmic NLB are composed of prenucleolar material that failed to attach to chromosomes.